Retrospective analysis of cardiovascular involvement in patients with systemic amyloidosis - E. V. Reznik; E. A. Stepanova; T.L. Nguyen; I. O. Sirenova; A. V. Salikov; I. G. Nikitin (Кардиоваскулярная терапия и профилактика, 2021)
Amyloidosis is a heterogeneous group of the diseases caused by the extracellular deposition of amyloid in various organs including a cardiovascular system.Aim. To study the cardiovascular damage in patients with systemic amyloidosis.Material and methods. A retrospective assessment of 38 cases of systemic amyloidosis was carried out. Diagnosis was verified by biopsy in 57,9% (27,3% of these cases were then confirmed by autopsy) and autopsy in 42,1% of patients. Congo red stain and polarized-light microscopy were used. The systemic nature of lesion was diagnosed in the positive biopsies of two or more localizations or in the positive biopsy of one localization in the combination with the clinical picture of amyloidosis at least one organ. Median (interquartile range) of age was 72,5 (64-84) years (women, 65,8%; men, 34,2%).Results. In the medical history, 81,6% of patients with systemic amyloidosis had hypertension, 52,6% — coronary artery disease, 34,2% — myocardial infarction, 36,8% — type 2 diabetes, 44,7% — atrial fibrillation, 26,3% — conduction disorders. Also 13,2% of patients had an implanted pacemaker. According to the electrocardiography, 42,3% of patients had a low QRS voltage. According to echocardiography, left ventricular (LV) hypertrophy was detected in 94,7% of patients. In addition, 31,6% of patients had signs of granular sparkling myocardial appearance, 20% — impaired local LV contractility, 77,8% — increased pulmonary artery reassure, 28,6% — LV diastolic dysfunction, 14,3% — normal diastolic function. LV ejection fraction (LVEF) was 55 (44,5-55)%. LVEF <40% was detected in 15%, 4050% — in 20%, >50% — in 65% of patients. Heart failure was indicated in 71,1% of patients with systemic amyloidosis, chronic kidney disease (CKD) — in 95% of patients. The estimated glomerular filtration rate (CKD-EPI) was 21,2 (13,1-40) ml/min/1,73 m2. Proteinuria (1,1 (0,5-3,0) g/l) was detected in 88,9% of patients. Nephrotic syndrome occurred in 27,8% of patients.Conclusion. Patients with cardiovascular lesions of unclear etiology, especially in the presence of LV wall thickening, preserved LVEF, stage 4-5 CKD and proteinuria, require screening for systemic amyloidosis.